PENERAPAN MODIFIED CERTAINTY FACTOR DALAM SISTEM PAKAR TES KEPRIBADIAN FLAG - Romy O. D. Djami; Sebastianus Adi Santoso Mola; Tiwuk Widiastuti (Universitas Nusa Cendana, 2018)
Expert system is one of artificial intelligence engines that is using specific knowledge of an expert to solve a specific problem. In this study, the expert system is built to implement FLAG personality test using Modified Certainty Factor method in order to help counselee knowing his personality type and the careers suitable for him. Knowledge source for this system is obtained from the book Tes Bakat Anda (Test Your Own Aptitude) by Jim Barrett and Geoff Williams (2002) along with several consultations with Irianti Agustina, S.Pd., M.Pd. and Dra. Sri Rahayu Djami. This system is able to provide the output in the form of personality type of the counselee as well as career recommendations suitable for him. Based on study on 141 data of counselees, the results are: By using Modified Certainty Factor, this expert system has accuracy of 83.69%, and provides more certain output than the output provided by the conventional FLAG. Therefore, researcher recommends the using of Modified Certainty Factor method to improve any other personality test which still has not given certain output.